ChemInform Abstract: Organocatalytic Activation of the Leaving Group in the Intramolecular Asymmetric SN2′ Reaction. Issue 45 (November 2015) - Kuroda, Yusuke; Harada, Shingo; Oonishi, Akinori; Yamaoka, Yousuke; Yamada, Ken‐ichi; Takasu, Kiyosei
Abstract 2‐Vinyl‐pyrrolidines bearing various substituents are highly enantioselectively obtained by an intramolecular metal‐free allylic alkylation.